1978
DOI: 10.1107/s0567739478014515
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the incident beam on integrated intensities in X-ray energy-dispersive diffractometry

Abstract: Polarization measurements of the primary X-ray beam produced by thick copper and tungsten anodes are reported and formulas derived for integrated intensities of Bragg reflections in energy-dispersive diffractometry with the polarization of the primary beam taken into account. It was found that for an angle of 45° between the scattering plane and the plane containing the electron beam and the primary beam, the influence of polarization vanishes, while it increases as the angle changes from 45 ° to either 0 or 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Moreover, because of the low scatter angle involved for the present experiment, it was found that even the largest absolute value of polarization measured by Olsen et al (1978) would only bring a maximum correction of less than 0.5% to the highest energy components.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, because of the low scatter angle involved for the present experiment, it was found that even the largest absolute value of polarization measured by Olsen et al (1978) would only bring a maximum correction of less than 0.5% to the highest energy components.…”
Section: Discussionmentioning
confidence: 59%
“…Since the polarization P(E) is almost constant in our energy range (Olsen, Buras & Jensen, 1978), an approximation Cr(E , O) ~-Cp(O) holds. Thus the intensity distribution l(s, Oi) at 0i is obtained from (3).…”
Section: Data Treatmentmentioning
confidence: 93%
“…2 E' E 2 (6) was found to be significantly E dependent at high angles [IO,52].To avoid this complication it is recommended to tilt the X-ray tube 45 0 away from the plane which includes incident and diffracted beams. The polarization factor is then independent of E, so that if we define p piE} (7) the expression (3) becomes much simplified:…”
Section: Data Reductionmentioning
confidence: 99%